Progressive pseudo-rheumatoid dysplasia -a rare genetic disorder: Case Report - Chowdhury, Md Faizul Islam; Shova, Shamima Sharmin; Monami, Afia Zahin; Alam, Rajibul; Rahman, M Ekhlasur (Anwer Khan Modern Medical College Journal, 2021)
Progressive pseudorheumatoid dysplasia (PPRD), also known as spondyloepiphyseal dysplasia tarda with progressive arthropathy (SEDT-PA), is an autosomal recessive disorder, resulting from mutations in the WNT1-inducible signaling pathway protein 3 (WISP3) gene involving the axial skeleton as well as small peripheral joints. Because of rarity here we present a case of 14-year-old boy, 1st issue of consanguineous parents who was presented with pain & gradual development of contracture in 3rd distal interphalangeal joint of right hand when he was 4-year-old, then gradual involvement of other interphalangeal joints of hands, bilateral wrists, elbows, shoulder, knees &ankles occurred over years with the development of contractures and restricted movement. For last few years, he developed difficulty in walking. Clinically spinal scoliosis and coxa vara was present. Mobility of spines and multiple joints including proximal & distal interphalangeal joints of hands, wrists, elbows, shoulders, knees, ankles were restricted with flexion contractures. The gait of the patient was limping. Radiological evaluation showed osteopenia in X-ray of pelvis with both hip joints and both knee joints. Generalized osteopenia, fusiform swelling in distal interphalangeal joint, flexion deformity in distal interphalangeal joint of middle and ring fingers of both hand was shown in X-ray of both hands. MRI of lumbosacral spine showed dorso-lumbar vertebral bodies dysplastic with anterior wedging producing bullet nose. Superior epiphyseal deformity was also noted in lower dorsal bodies suggestive of spondyloepiphyseal dysplasia of dorso-lumbar spine. Genetic study showed homozygous nonsense variation in exon 5 of the WISP3 gene suggestive pathogenic variant. Finally, he was diagnosed as a case of PPRD and treated with physiotherapy, family counseling, and anti-inflammatory medications. AKMMC J 2022; 13(1) : 52-55